Corporate Social Responsibilty: Exxonmobil's Form of Liability as a Foreign Investor of Mining Companies in Indonesia - Ar Raidah, Salsabila Fakhriyyah; Ningsih, Ekawati Rahayu (BISNIS, 2021)
AbstractCurrently, the business sector that is being intensified by the Indonesian government is the mining sector which is aimed at increasing state revenue. The state revenue aims to prosper the people's welfare, which is guaranteed by the constitution of Article 33 paragraph (3) of the 1945 Constitution of the Republic of Indonesia which states that the land, water and natural resources in it are state control designated in the event that prosperity of the people. In developing the mining business sector, Indonesia needs cooperation from foreign investors to adequately fulfill various needs. In developing the mining business sector, Indonesia needs cooperation from foreign investors to adequately fulfill various needs. In developing the mining business sector, Indonesia needs cooperation from foreign investors to adequately fulfill various needs. Therefore, Indonesia is cooperating with a company from America, namely PT. ExxonMobil. However, in the implementation of their investment activities, there are many problems, especially with the communities around the mining area. Therefore, this study aims to analyze the form of PT. ExxonMobil's responsibility for investing in Indonesia using normative juridical research methods..